(untitled) (Argos, 2025)
The present paper shows, through the literary and ethic-pedagogical analysis of Διδάσκαλος, Herodas’ third mime, how family and school are educational agents which in times of moral crisis stumble. This research work also discovers the relevance of the problem suffered by Metrotime, Cotalo’s mother, and by Lamprisco, a teacher. They both fail when they have to guide and correct a stubborn and bold teenager.